Salivary characteristics of diabetic children - López María Elena; Colloca María Eugenia; Páez Rafael Gustavo; Schallmach Judit Nora; Koss Myriam Adriana; Chervonagura Amalia (Fundação Odontológica de Ribeirão Preto, 2003)
Salivary components may suffer variations that can be detected by chemical determinations. The aim of this work was to determine physical and biochemical characteristics of the saliva of a group of diabetic children compared to those of a control group. Relation to oral health indices was also determined. Twenty diabetic children (3-15-years-old) and 21 control children (5-12-years-old) were included in this study. Total proteins, sugars and calcium were determined by colorimetric methods, and glucose, urea, alpha-amylase and acid phosphatase by enzymatic methods. Our results demonstrated that acidic pH, diminished salivary flow rate and excess foam are usually present in saliva of diabetic children. Total sugars, glucose, urea and total proteins were greater in diabetic patients than controls, while calcium values were decreased. These differences were confirmed by the discrimination test. Diabetic children have higher DMFT-dmft-deft and DMFS-dmfs-defs values compared to those of the control children despite their lower sugar intake. Some salivary components in addition to the diminished flow rate could be involved in the characterization of the oral health state of diabetic children.